EFFECTS OF SUGAR TYPE AND CONCENTRATION ON THE CHARACTERISTICS OF FERMENTED TURI (SESBANIA GRANDIFLORA (L.) POIR) MILK - Zhang, Sutikno; Rizal, Samsul; ., Marniza (Emirates Journal of Food and Agriculture, 2013)
Fermented milk products are widely consumed for their positive health image, which can be further enhanced by the addition of probiotic bacteria with therapeutic properties. One of the fermented milk products is fermented turi-milk; however, the turi milk has unpleasant off flavor and sour taste. The objective of this study was to determine the best treatment in producing fermented turi-milks with acceptable flavor and taste. Two treatments were arranged in Randomized Block Design with 3 replications. The first treatment was sugar types which consisted of sucrose, glucose, and a sucrose-glucose mixture at a ratio of 1:1. The second treatment was concentrations of sugar consisting of 29.25%, 35.75%, 42.25%, and 48.75% (w/v). Clean turi seeds were submerged in 0.5% NaHCO3 solution at 80oC for 15 minutes, crushed using a blender, and filtered with filter cloth to obtain turi milk. The turi milk was added with 10% skim milk powder and 4% glucose, inoculated with Lactobacillus casei subsp. rhamnosus, and then incubated at 37oC for 96 hours to produce fermented turi-milks. The fermented turi-milks were added with sugar at different concentrations and then stored at refrigerate temperature for 12 days. After storing for 12 days, samples of the turi-milks were taken, and analyzed to determine their pH, total acid bacteria, and sensory characteristics. Result of this study showed that adding sucrose at a concentration of 35.75% (w/v) was the best treatment to produce fermented turi-milk with acceptable flavor and taste. The best fermented turi-milk had a pH of 3.71, a total lactic acid bacteria of 3.62 x 1011 cfu/g, a taste scores of 3.75, a flavor score of 3.3, and an overall acceptance score of 3.75 (out of 5 scales).